1997
DOI: 10.1172/jci119146
|View full text |Cite
|
Sign up to set email alerts
|

Voltage-gated calcium channel currents in human coronary myocytes. Regulation by cyclic GMP and nitric oxide.

Abstract: Voltage-gated Ca 2 ϩ channels contribute to the maintenance of contractile tone in vascular myocytes and are potential targets for vasodilating agents. There is no information available about their nature and regulation in human coronary arteries. We used the whole-cell voltage-clamp technique to characterize Ca 2 ϩ -channel currents immediately after enzymatic dissociation and after primary culture of coronary myocytes taken from heart transplant patients. We recorded a dihydropyridine-sensitive L-type curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(55 citation statements)
references
References 45 publications
4
50
0
Order By: Relevance
“…cGMP accumulation has been shown to decrease cardiac contractility via reduction of myofilament sensitivity to calcium. 46,47 In addition, we observed increased eNOS expression in both strains treated with DOCA-salt, which tended to be greater in iNOSϪ/Ϫ (Pϭ0.05). Increased eNOS expression may be a compensatory mechanism for increased vascular resistance and decreased myocardial perfusion.…”
Section: Sun Et Al Role Of Inos In Doca-salt Hypertension 1359mentioning
confidence: 71%
“…cGMP accumulation has been shown to decrease cardiac contractility via reduction of myofilament sensitivity to calcium. 46,47 In addition, we observed increased eNOS expression in both strains treated with DOCA-salt, which tended to be greater in iNOSϪ/Ϫ (Pϭ0.05). Increased eNOS expression may be a compensatory mechanism for increased vascular resistance and decreased myocardial perfusion.…”
Section: Sun Et Al Role Of Inos In Doca-salt Hypertension 1359mentioning
confidence: 71%
“…This study also reported that whole cell LVA currents could only be observed in half of the cells. In contrast, LVA currents were never detected in freshly isolated coronary SMCs from rabbits (269) or humans (332). LVA currents were found if the cells were cultured, and these currents appear to be T type based on their voltage dependence and 1:1 conductance of Ca 2ϩ and Ba 2ϩ (332).…”
Section: E Smooth Musclementioning
confidence: 99%
“…LVA currents have been found in the following arterial SMCs: coronary (130,281,332), aortic (3), mesenteric (150,311,372), rabbit ear (34), rat tail (327,428), and middle cerebral arterioles (167). RT-PCR detected the expression of both Ca v 3.1 and Ca v 3.2 in rat mesenteric arterioles (150).…”
Section: E Smooth Musclementioning
confidence: 99%
See 1 more Smart Citation
“…This pathway is activated by NO and leads to the formation of cGMP. L-type Ca 2 þ channel activity is inhibited by cGMP/cGMP-dependent protein kinase (PKG) stimulation in a wide variety of smooth muscles (canine colon, Koh & Sanders, 1996; human coronary artery, Quignard et al, 1997;rabbit portal vein, Ruiz-Velasco et al, 1998). This is thought to result from PKG causing the phosphorylation of an inhibitory binding site associated with L-type Ca 2 þ channels (Ruiz-Velasco et al, 1998).…”
Section: Introductionmentioning
confidence: 99%